High prevalence of low vitamin D status in the Czech Republic: a retrospective study of 119,925 participants - Holmannova, Drahomira; Borsky, Pavel; Kremlacek, Jan; Krejsek, Jan; Hodacova, Lenka; Cizkova, Anabela; Fiala, Zdenek; Borska, Lenka (European journal of clinical nutrition, 2025)
OBJECTIVES: Given the high worldwide prevalence of vitamin D deficiency and its role in numerous diseases affecting mortality and morbidity, this study seeks to determine the prevalence of low 25-hydroxyvitamin D levels in the Czech Republic, where population-level data are currently lacking. STUDY DESIGN: This retrospective study utilized a large dataset to analyze 25-hydroxyvitamin D levels over an extended period. METHODS: We analyzed data from 119,925 individuals aged 0-100 years categorizing them as sufficient (75-250 nmol/L), insufficient (50-75 nmol/L), or deficient (<50 nmol/L). We also examined levels of CRP, homocysteine, and their correlations with 25-hydroxyvitamin D levels across age groups. Age, sex, sampling month, sunlight exposure (monthly and annual), and influenza virus positivity were assessed for their relationship with the 25-hydroxyvitamin D levels. RESULTS: The study found a high prevalence of 25-hydroxyvitamin D inadequacy, with sufficient levels observed in 65.6% of infants (0-12 months). The lowest prevalence of sufficiency was in the 6-15 years (19.2%) and 16-30 years (22.1%) groups. The highest deficiency prevalence was in the 91-100 years group (51.8%). 25-hydroxyvitamin D levels in all age groups and both sexes correlated with all selected parameters. Lower sun exposure, higher flu virus positivity, male gender, and elevated homocysteine and CRP levels were negatively correlated with 25-hydroxyvitamin D levels. CONCLUSIONS: The prevalence of 25-hydroxyvitamin D inadequacy in the Czech Republic is high. It is advisable to consider testing, monitoring, and providing medical recommendations for vitamin D supplementation as part of health prevention strategies in the general population.
Keywords: Young Adult; sluneční záření; Male; retrospektivní studie; Child, Preschool; Vitamin D Deficiency; mladý dospělý; Adolescent; Infant; Česká republika; Child; dítě; prevalence; Adult; C-reaktivní protein; Aged; dospělí; mužské pohlaví; senioři; vitamin D; mladiství; Czech Republic; novorozenec; předškolní dítě; senioři nad 80 let; homocystein; lidé; ženské pohlaví; Humans; Infant, Newborn; kojenec; Prevalence; Aged, 80 and over; C-Reactive Protein; Retrospective Studies; Vitamin D; Female; nedostatek vitaminu D; lidé středního věku; Homocysteine; Middle Aged; Sunlight